Treatment of Helicobacter pylori infection 2017. (September 2017) - O'Connor, Anthony; Lamarque, Dominique; Gisbert, Javier P.; O'Morain, Colm
Abstract: This review summarizes important studies regarding Helicobacter pylori therapy published from April 2016 to April 2017. The main themes that emerge involve studies assessing the efficacy of bismuth and nonbismuth quadruple regimens. While in recent years, much of the emphasis on the use of bismuth has focussed on its utility in a second‐line setting, an increasing number of studies this year have shown excellent efficacy in first‐line therapy. The efficacy of bismuth as a second‐line after sequential and concomitant therapy was particularly noteworthy. Antibiotic resistance was more intensely studied this year than for a long time, and definite trends are presented regarding an increase in resistance, including the fact that clarithromycin resistance in particular is now at a level where the continued use of clarithromycin triple therapy first‐line as a mainstream treatment is not recommended. Another exciting trend to emerge this year is the utility of vonoprazan as an alternative to PPI therapy, especially in resistant and difficult‐to‐treat groups.